The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7759/cureus.35276
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pembrolizumab-Induced Diabetic Ketoacidosis and Hyperthyroidism in a Patient With Recurrent Esophageal Adenocarcinoma

Abstract: Immune checkpoint inhibitors (ICI) such as program cell death protein 1 (PD-1) inhibitors are widely used for the treatment of patients with recurrent, locally advanced or metastatic, gastric or gastroesophageal (GE) junction adenocarcinoma. Immune-related adverse events (irAE) such as endocrinopathies have been reported after patients received ICI. We report a case of pembrolizumab-induced hyperthyroidism and type 1 diabetes mellitus (DM1) presenting with diabetic ketoacidosis (DKA). A 53-year-old African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Available evidence on the association of pancreatic autoantibodies with ICI-related diabetes is inconsistent. Some authors ( 17 ) have reported that most East Asian patients are negative for these autoantibodies, as in our case 1, whereas others have documented positivity for at least one pancreatic autoantibody, most commonly glutamic acid decarboxylase antibody, in 30–50% of cases ( 18 ). In addition, certain human leukocyte antigen (HLA) genotypes (e.g., the DR3-DQ2 and DR4-DQ8 haplotypes) are known to confer susceptibility to (fulminant) type 1 diabetes ( 19 ), and they (mainly DR4) have been detected in about 61% of patients with ICI-related diabetes ( 20 ).…”
Section: Ici-related Diabetesmentioning
confidence: 53%
“…Available evidence on the association of pancreatic autoantibodies with ICI-related diabetes is inconsistent. Some authors ( 17 ) have reported that most East Asian patients are negative for these autoantibodies, as in our case 1, whereas others have documented positivity for at least one pancreatic autoantibody, most commonly glutamic acid decarboxylase antibody, in 30–50% of cases ( 18 ). In addition, certain human leukocyte antigen (HLA) genotypes (e.g., the DR3-DQ2 and DR4-DQ8 haplotypes) are known to confer susceptibility to (fulminant) type 1 diabetes ( 19 ), and they (mainly DR4) have been detected in about 61% of patients with ICI-related diabetes ( 20 ).…”
Section: Ici-related Diabetesmentioning
confidence: 53%